Sexual victimization against transgender women in prison: consent and coercion in context - Jenness, Valerie (Criminology, 2019)
In this article, we conjoin two long‐standing lines of inquiry in criminology—the study of prison life and the study of sexual assault—by using original qualitative and quantitative data from 315 transgender women incarcerated in 27 California men's prisons. In so doing, we advance an analysis of the factors and processes that shape their experience of sexual victimization in prison. The results of qualitative analysis of 198 reported incidents of sexual victimization exhibit a range of types of sexual victimization experienced by transgender women in prison and reveal the centrality of relationships to their experiences of victimization. Findings from logistic regression models buttress the qualitative results, highlighting a factor that consistently and powerfully indicates vulnerability to sexual victimization is involvement in consensual sexual relationships with male prisoners. Together, the data demonstrate the prominence of intimate partner violence in prison, complicate the distinction between consent and unwanted sexual experiences in the lives of transgender women in prisons for men, and shine a light on the workings of gender in a total institution that privileges heteronormativity at the expense of the safety of transgender women in prisons for men. We discuss the implications of our findings in light of timely policy concerns.